2010
DOI: 10.19030/cier.v3i6.209
|View full text |Cite
|
Sign up to set email alerts
|

The Development Of Expert Learners In The Classroom

Abstract: The term ‘expert learner’ refers to students who are actively engaged with the materials learned and take responsibility for their own learning. Literature reviews suggested the use of metacognitive approach to help develop students to become expert learners. Research on development of expert learners can be traced from movements that focused on the importance of learning strategies and “learning how to learn” approach. Some researchers combined the role of teachers and students in formulating a framework on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Metacognitive reflection helps students to be aware of the learning process through which it passes (Beyer, 1988). In this study, among the activities involved in the process of metacognitive reflection is to evaluate the achievement of learning outcomes and learning content (the content of a subject) and the process of learning how to learn (Saemah et al, 2010). Metacognitive reflection practices through metacognitive strategies technique encourage students to make self-reflection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metacognitive reflection helps students to be aware of the learning process through which it passes (Beyer, 1988). In this study, among the activities involved in the process of metacognitive reflection is to evaluate the achievement of learning outcomes and learning content (the content of a subject) and the process of learning how to learn (Saemah et al, 2010). Metacognitive reflection practices through metacognitive strategies technique encourage students to make self-reflection.…”
Section: Discussionmentioning
confidence: 99%
“…Review of past studies revealed that students did not have thinking and learning management skills (Shahlan, 2012). In addition, there is a lack of metacognitive knowledge namely declarative knowledge, conditional knowledge and procedural knowledge in writing tasks (Saemah, 2010). It is not known how students capitalized this kind of thinking skills in their writing activity.…”
Section: Introductionmentioning
confidence: 99%
“…Woolfolk (2008) revealed three characteristics of expert learners: they focus their attention on materials learned, give the effort to process the information deeply, and take responsibility for their learning. Rahman et al (2010) pointed out one of the important characteristics of expert learners: controlling their learning through meta-attention and meta-comprehension. These authors clarified expert learners as having a specific goal at the beginning of the lesson to help them focus and, consequently, monitor and evaluate their learning outcomes.…”
Section: Characteristics Of Expert Learners In the Context Of Inclusive Educationmentioning
confidence: 99%